1991
DOI: 10.1002/ijc.2910480310
|View full text |Cite
|
Sign up to set email alerts
|

A case‐control study of gastric cancer and diet in Italy. III. Risk patterns by histologic type

Abstract: In a case-control study of gastric cancer (GC) in high-risk and low-risk areas of Italy, 923 GCs were systematically categorized by one pathologist according to the Lauren classification distinguishing 2 main histologic types, intestinal (55%) and diffuse (23%). Intestinal types outnumbered diffuse types by a 3 to 1 margin in high-risk regions in the north-central part of the country, while both types occurred at nearly equal rates in low-risk areas. Intestinal types also occurred relatively more frequently at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 20 publications
3
55
0
1
Order By: Relevance
“…Of the previous studies, all of them case -control, that have considered GC pathology in relation to dietary carotenoids, some have failed to detect any associations or differences by subtype (Boeing et al, 1991;Buiatti et al, 1991), whereas others have shown mixed results (Gonzalez et al, 1994;Harrison et al, 1997;Ekstrom et al, 2000), suggesting that the effects of carotenoids might be similar in both histological subtypes. In the present study, none of the analytes, with the possible exception of a-tocopherol, showed any significant effects by anatomical subsite or histological subtype.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Of the previous studies, all of them case -control, that have considered GC pathology in relation to dietary carotenoids, some have failed to detect any associations or differences by subtype (Boeing et al, 1991;Buiatti et al, 1991), whereas others have shown mixed results (Gonzalez et al, 1994;Harrison et al, 1997;Ekstrom et al, 2000), suggesting that the effects of carotenoids might be similar in both histological subtypes. In the present study, none of the analytes, with the possible exception of a-tocopherol, showed any significant effects by anatomical subsite or histological subtype.…”
Section: Discussionmentioning
confidence: 96%
“…Several case -control studies have shown strong inverse associations between GC risk and higher consumption of some of these nutrients (Buiatti et al, 1990(Buiatti et al, , 1991Gonzalez et al, 1994;Hansson et al, 1994;Ekstrom et al, 2000). Results from prospective dietary studies are conflicting and show either a strong protection (Zheng et al, 1995) or no clear inverse associations between the dietary intake of carotenoids and GC risk (Ocke et al, 1995;Botterweck et al, 2000b).…”
mentioning
confidence: 99%
“…In many studies, consumption of food rich in nitrate and nitrite, smoked food, a high salt diet and a 4 A kind of kimchi prepared with salted radish and the same subingredients as Baiechu kimchi.- 5 A kind of kimchi prepared with radish and a large quantity of salt water.-*p Ͻ 0.05; **p Ͻ 0.01. high starch diet have seemed to be risk factors for GC, whereas high consumption of fresh fruits and vegetables, milk and milk products have seemed to be protective. [5][6][7][8][9][10][11][12][13][14][15] Although controversial, it has been reported that dietary fat, meats, fish, seasonings and beverages such as coffee and tea are also associated with increased risk of GC. 6,10,11,15,24 Intake of charcoal grilled beef significantly increased the risk of GC in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on the relationship between diet and GC have suggested that foods rich in nitrate or nitrite, a high salt diet, smoked meat or fish and a high carbohydrate diet increase the risk of GC, whereas high consumption of fresh vegetables, fruits and dairy products decreases the risk of GC, although the findings are not always consistent. [5][6][7][8][9][10][11][12][13][14][15] Dietary habits of Korean people can be characterized as a high intake of salty foods and carbohydrates and a higher intake of cooked rather than fresh vegetables. For this reason, it is necessary to investigate the effect of dietary factors on GC in Korea.…”
mentioning
confidence: 99%
“…The large Italian case-control study (Buiatti et al, 1991) is one of the few studies to find this. In contrast the population studies and the majority of casecontrol studies of gastric cancer show meat intake to be inversely related to cancer risk (Table 5).…”
Section: Human Epidemiology Of Meat and Colorectal Cancermentioning
confidence: 98%